1982
DOI: 10.1021/i300006a024
|View full text |Cite
|
Sign up to set email alerts
|

Process for chemical separation of the three main components of lignocellulosic biomass

Abstract: Ind. Eng. Chem. Prod. Res. Dev. 1902, 21, 309-314 309 On several occasions, after carburetor ice was allowed to form in the carburetor of one or both engines while using stock fuel, the fuel supply was switched to a tank containing EGME-treated fuel. In every case power was immediately regained. Thus EGME-treated fuel would also serve as a de-icing agent.On five occasions, carburetor ice was encountered with both engines operating on stock fuel, but with different mixture settings. As discussed earlier, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 6 publications
0
11
0
2
Order By: Relevance
“…Figure 8 shows that fractionation of lignocellulosic biomass into its three major components, cellulose, hemicelluloses and lignin. It has been proposed as the first step of LCF refining to high value-added products [108]. Achieving high fractionation yields and maintaining the integrity of the macromolecular fractionation products are of major importance regarding the effectiveness of the whole refining process [109].…”
Section: Definitionmentioning
confidence: 99%
“…Figure 8 shows that fractionation of lignocellulosic biomass into its three major components, cellulose, hemicelluloses and lignin. It has been proposed as the first step of LCF refining to high value-added products [108]. Achieving high fractionation yields and maintaining the integrity of the macromolecular fractionation products are of major importance regarding the effectiveness of the whole refining process [109].…”
Section: Definitionmentioning
confidence: 99%
“…Prehydrolysis is by far the best method to separate hemicellulose as a sugar solution. In almost all proposed processes there is a step, where a contact with an acidic aqueous phase is employed for that purpose (Aronovsky & Gortner, 1936 laboratory helped to investigate the effects of this pre hydrolytic pretreatment (Koukios & Nicolacopoulos, 1979;Koukios, 1981;Koukios & Valkanas, 1982). Experiments on wheat (Triticum sativum) straw have shown that pentosan hydrolysis under strong conditions follows pseudo-first order kinetics with a rate constant given by the equation (Koukios, 1981) kp = 1.95 .…”
Section: Fractionation Of Lignocellulosic Biomassmentioning
confidence: 99%
“…C~~~~ . e -~~ (4) Under those conditions, 90% of the original hemicellulose can be recovered as reducing sugars (Koukios & Valkanas, 1982). At the same time, the structure of the residue is significantly modified: a considerable fraction of cellulose, as high as 30% of the original value, is depolymerized also following pseudo-first order kinetics, and more than 50% of the original lignin becomes soluble in organic solvents, possibly after depolymerization, according to the same apparent kinetic pattern (Koukios, 1981).…”
Section: Fractionation Of Lignocellulosic Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, inexpensive fractionation of lignocellulosic material into its components could significantly improve the overall efficiency of biomass utilization [9,10]. This is essential to develop an economically viable biorefinery process [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%